2021
DOI: 10.2147/ott.s317403
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Circ-SHPRH in Cancer

Abstract: Purpose: Circ-SHPRH is a circular RNA that can regulate the expression of target genes by sponging microRNAs (miRNAs) or translating tumor suppressor proteins. Recent studies have suggested that circ-SHPRH may play a role in the development of tumors and cancers. Hence, this paper aimed to review the biological characteristics, molecular mechanisms, and potential clinical significance of circ-SHPRH in a variety of tumors and to evaluate its potential as a new diagnostic and prognostic biomarker. Methods: Numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 99 publications
0
3
0
Order By: Relevance
“…However, while it was suggested that this protein operated by protecting the full-length SHPRH protein from degradation, no further investigation was done on the function of full-length SHPRH itself in glioblastoma [93]. Similarly, while there has been a recent emergence of evidence suggesting that circ-SHPRH operates as a tumor suppressor gene in a multitude of other cancerswhere its downregulation in turn promotes cancer development and progression by affecting a variety of oncogenic processesthe evaluation of its effect on full-length SHPRH in these cancers has yet to be conducted [94]. As such, despite the overwhelming evidence suggesting that full-length SHPRH may be a tumor suppressor in multiple cancer types, the functional characterization of it as a tumor suppressor gene has yet to be exhibited.…”
Section: Discussionmentioning
confidence: 99%
“…However, while it was suggested that this protein operated by protecting the full-length SHPRH protein from degradation, no further investigation was done on the function of full-length SHPRH itself in glioblastoma [93]. Similarly, while there has been a recent emergence of evidence suggesting that circ-SHPRH operates as a tumor suppressor gene in a multitude of other cancerswhere its downregulation in turn promotes cancer development and progression by affecting a variety of oncogenic processesthe evaluation of its effect on full-length SHPRH in these cancers has yet to be conducted [94]. As such, despite the overwhelming evidence suggesting that full-length SHPRH may be a tumor suppressor in multiple cancer types, the functional characterization of it as a tumor suppressor gene has yet to be exhibited.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously found that circRNAs play vital effects in various cancer progression, including GC. 20 For example, overexpression of circHECTD1 advanced GC cell malignant phenotype by energizing glutaminolysis metabolites. 21 Circ_0002570 knockdown could suppress cell proliferation and metastasis in vitro, and restrain tumor growth in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously found that circRNAs play vital effects in various cancer progression, including GC 20 . For example, overexpression of circHECTD1 advanced GC cell malignant phenotype by energizing glutaminolysis metabolites 21 .…”
Section: Discussionmentioning
confidence: 99%